Fulminant Course of Neuromyelitis Optica in a Patient With Anti-MDA5 Antibody-Positive Dermatomyositis: A Case Report - Kang, You-Ri; Kim, Kun-Hee; Nam, Tai-Seung; Lee, Kyung-Hwa; Kang, Kyung Wook; Lee, Seung-Jin; Choi, Seok-Yong; Chandrasekaran, Gopalakrishnan; Kim, Myeong-Kyu (Frontiers in Medicine, 2020)
Anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody is a myositis-specific marker detected in clinically amyopathic dermatomyositis (DM). DM with anti-MDA5 antibody can be accompanied by rapidly progressive interstitial lung disease (RP-ILD) and other autoimmune disorders. Until now, only one case of neuromyelitis optica (NMO) with anti-MDA5-positive DM has been reported worldwide, in which the patient achieved a favorable outcome with intensive immunotherapy. We report a case of NMO in a patient with anti-MDA5-positive DM complicated by ILD and rheumatoid arthritis. Our patient experienced a fulminant course of NMO, rather than RP-ILD, in the presence of hyperferritinemia, which resulted in profound neurological sequelae despite immunotherapy including rituximab.